2009
DOI: 10.1097/cji.0b013e3181a01abb
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Dendritic Cells and CD34+CD38− Acute Myeloid Leukemia (AML) Cells Potentiates Targeting AML-initiating Cells by Specific CTL Induction

Abstract: Distinct leukemia-initiating cells (L-ICs) represent a critical target for therapeutic intervention of acute myeloid leukemia (AML). A potential strategy to eradicate L-ICs is to generate L-IC-specific cytotoxic T lymphocytes (CTLs). However, owing to rarity and immortality of L-ICs, it is difficult for antigen-presenting cells to capture L-ICs for specific antigen presentation. Here, we report a novel approach by fusing allogeneic dendritic cells (DCs) and CD34CD38 AML progenitor cells, through which specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, only two of these patients were long‐term survivors [82]. Alternatively, DC have been generated from AML patients in remission and made more antigenic by fusion with AML blasts [83], exposure to AML lysates or peptide antigens or transfection with RNA [84]. A clinical trial with a monocyte‐derived DC loaded with mRNA for Wilms tumour‐1 (WT1) antigen is under way [85].…”
Section: Developments In Immunotherapy Of Amlmentioning
confidence: 99%
“…However, only two of these patients were long‐term survivors [82]. Alternatively, DC have been generated from AML patients in remission and made more antigenic by fusion with AML blasts [83], exposure to AML lysates or peptide antigens or transfection with RNA [84]. A clinical trial with a monocyte‐derived DC loaded with mRNA for Wilms tumour‐1 (WT1) antigen is under way [85].…”
Section: Developments In Immunotherapy Of Amlmentioning
confidence: 99%
“…Dendritic cells (DCs) are major antigen-presenting cells (APCs) that recognize and present antigens to T cells, inducing an antitumour T cell effect. 5 Cytokine-induced killer (CIK) cells are immune effector cells that play a potential role in adoptive cell immunotherapy and exhibit potent cytotoxicity against a variety of autologous and allogeneic AML cells. 6 Thus, DCs present antigens to T cells initiating an antitumour response by activating cytotoxic T cells and CIK cells, which can kill tumour cells by acting on autologous cytotoxicity and secreting cytokines.…”
Section: Dendritic and Cytokine-induced Killer Cells In Immunotherapy In Amlmentioning
confidence: 99%
“…6 Thus, DCs present antigens to T cells initiating an antitumour response by activating cytotoxic T cells and CIK cells, which can kill tumour cells by acting on autologous cytotoxicity and secreting cytokines. 5,7 Some in vivo and in vitro animal studies have reported that the combination of CIK cells with relevant chemotherapy enhanced antitumour effectiveness in human drug-resistant cancer cell lines and that this was not influenced by the multipledrug resistance of the tumour. 8,9 In previous studies, venous transfusion of DCs and CIK cells was performed after complete haematological remission had occurred in order to mitigate the negative impact of chemotherapy and immunosuppression on the body's immune system response to DC and CIK cell therapy.…”
Section: Dendritic and Cytokine-induced Killer Cells In Immunotherapy In Amlmentioning
confidence: 99%
“…The efficacy of antitumor immunity induced by DC/tumor fusion vaccines has been demonstrated in murine models using melanoma [24–32], colorectal [17, 30, 31, 3341], breast [4247], esophageal [48], pancreatic [49, 50], hepatocellular [5155], lung [22, 41, 56–59], renal cell [60] carcinoma, sarcoma [61–66], myeloma [6774], mastocytoma [75], lymphoma [76], and neuroblastoma [77]. The fusion cells generated with human DC and tumor cell also have the ability to present multiple tumor antigens, thus increasing the frequency of responding T cells and maximizing antitumor immunity capable of killing tumor targets such as colon [7884], gastric [85, 86], pancreatic [87], breast [47, 8893], laryngeal [94], ovarian [9597], lung [85, 98], prostate [99, 100], renal cell [101, 102], hepatocellular [103105] carcinoma, leukemia [106111], myeloma [112, 113], sarcoma [114, 115], melanoma [116119], glioma [120], and plasmacytoma [121]. …”
Section: Dc/tumor Fusion Vaccinesmentioning
confidence: 99%